Innovative celebrity endorsement and consumer purchase - SANKAR, DR. JEGANATHAN GOMATHI; MS. INDHUJA. M (The journal of contemporary issues in business and government, 2020)
The research paper titled to study about the impact of consumer buying behaviour on celebrity endorsement. The objective of the study to study and examine the purchase intention of celebrity endorsement in respect to brand quality, brand usage and brand recognition. The tools used in the study are frequency analysis, independent t-test, one-way ANOVA, regression analysis. It is found that consumer behaviour relates t the brand perception, brand quality and brand image.